Assessment of nurses approach to headache during triage in the emergency department - Santana, Claudia Cristina de Lira; Souza, Bruno Felipe Novaes de; Andrade, Juliana Ramos de; Valença, Marcelo Moraes (Headache Medicine, 2024)
Introduction: Nurses need a broad set of information and skills to properly assess patients during triage in the emergency department. Most healthcare services use the Manchester Triage System, developed in 1997, which improves care by ensuring that patients needing immediate attention receive priority according to the severity of their condition. Headache has its own pathway in this classification system, with the time to treatment varying based on pain intensity. Objective: To evaluate nurses' approach to headache during triage in the emergency department of a private hospital. Method: Data were retrospectively obtained from the Electronic Patient Record using a Business Intelligence tool. All visits from June 2024 were analyzed, including patients diagnosed with headache in the emergency department of a private hospital in Recife, which uses the Manchester Triage System. Variables assessed included the flowchart chosen by the nurse during triage, the color of the wristband assigned during risk classification, medical diagnoses, and characteristics of the patients' primary complaint. Results: Of the 7,464 visits, 361 (4.8%) were for patients with a medical diagnosis of headache and its variations. Of these, 258/361 (71.5%) reported headache as the primary complaint and were placed by the nurse in the "headache" flowchart. The remaining 103/361 (28.5%) were classified by the nurse in other flowcharts. Among patients classified in other flowcharts, 54 showed characteristics of migraine but were not correctly placed in the "headache" flowchart by the nurse. In this group, 14 patients were diagnosed with migraine without aura (G-43.0) and 40 with headache (R-51). A prevalence of the "adult malaise" flowchart (17/54; 31.5%) was observed among incorrectly classified patients. Most patients (333/361; 92.2%) received a green wristband, indicating a treatment time of up to 120 minutes. Conclusion: Although most patients were included by the nurse in the "headache" flowchart, a portion was still placed in different flowcharts despite presenting characteristics of migraine. This highlights the need to improve the classification of patients with headache.